Cloning, Expression, Purification, and Characterization of Clostridium botulinum Neurotoxin Serotype F Domains - Dulal, Santosh; Ban, Bhupal; Yang, Gi Hyoek; Jung, Hyun Ho (Nepal Journal of Biotechnology, 2012)
The use of recombinant BoNT domains has been proposed as a means to develop strategies to treat and prevent botulism. Here, details on the molecular cloning, protein expression, purification, and immunoreactivity of BoNT/F domains from Clostridium botulinum are presented. Initially, full-length synthetic genes encoding recombinant BoNT/F domains (catalytic, translocation, and receptor binding) were designed and cloned into Escherichia coli for expression. Recombinant proteins were then purified through GST affinity chromatography preceding elution of GST-free recombinant domains by thrombin protease. Soluble recombinant proteins encoding catalytic light chain and translocation N-terminal heavy chain were subsequently used to perform in vivo immunization. Polyclonal mouse antibodies specific to these domains were raised, confirmed by Western blot analysis and elevated immunoreactivity was identified through indirect ELISA. In conclusion, availability of the recombinant protein provides an effective system to study the immunological aspects of BoNT/F and corresponding applications in pathogen detection and vaccine candidacy. Keywords: Clostridium botulunium; Botulinum Neurotoxin Type F (BoNT/F) domains; cloning; recombinant protein expression; immunoreactivity DOI: http://dx.doi.org/10.3126/njb.v2i1.5634 Nepal Journal of Biotechnology Jan.2012, Vol.2(1): 1-15